Breaking The Silence: Civil society organizations promoting women’s personal security against sexual violence in Jombang Islamic boarding schools - Setyorini, Islamia Dewi; Andini, Amalia Nur (Salasika, 2023)
The prevalence of sexual violence against women (SVAW) in Indonesian Islamic boarding schools highlights that these institutions have not yet become safe spaces. The physical and psychological harm of sexual violence experienced by women poses a significant threat to their human security, a fundamental right that the state should ideally ensure. However, promoting personal security requires the collective support of society as a whole. This study focuses on Jombang Regency's pesantren (Islamic boarding schools), which is renowned as a city of Islamic education or “Kota Santri”. It explores the role of local civil society organizations (CSOs) in promoting personal security against sexual violence in these settings. Through qualitative methods such as in-depth interviews with CSOs’ representatives and a comprehensive literature review from 2017 to 2022, the research reveals that CSOs in Jombang Regency engage in prevention, protection, and empowerment. However, the roles are not fully optimized, particularly in terms of protection, due to limited implementation and a focus on case management. The findings highlight the importance of implementing binding policies to govern pesantren management and encourage active participation in preventing and addressing sexual violence within religious educational institutions. CSOs, islamic boarding school, personal security, pesantren, sexual violence against women